The utilization of Soybean for the production of lactic acid by lactococcus lactis IO-1 - Angela, Anak Usit. (Universiti Malaysia Sarawak, (UNIMAS), 2003)
Batch fennentation trials utilizing Lactococcus lactis 10-1 shows that different protein sources of either polipepton or its combination with soya bean exhibited only minimal differences in the amount of lactate yield at O.58g/g and O.59g/g respectively. In fermentation utilizing the combination of polipepton and soya bean results in higher residual glucose at 22.93g1L, thus needed longer period for complete consumption compared to only l.07g/L in polipepton. The maximum lactate production of po Ii pep ton and the combination of the protein were at 30.55gIL and 39.39gIL respectively, achieved after 48 hours of fermentation.